Čalbmi čalmmis ja suoldnečalmmit suoidnečalmmis - Jussi Ylikoski (Nordlyd, 2022)
North Saami čalbmi ‘eye’ (< Proto-Uralic *ćilmä) has cognates in all Uralic languages, and everywhere they refer to the visual organs of humans and animals. However, scholars have barely paid attention to the grammatical functions of čalbmi in compound-like formations such as suoldnečalbmi “dew eye”, suoidnečalbmi “grass eye”, varračalbmi “blood eye”, jiekŋačalbmi “ice eye”, vuoktačalbmi “hair eye” and muorječalbmi “berry eye”. This article examines such expressions as so-called singulatives – grammatical means for individuating a single referent from a group or mass (i.e., ‘a single drop of dew’, ‘a single blade of grass’, ‘a single drop of blood’, ‘a single crystal of ice’, ‘a single human hair’ and ‘a single berry’). The article mainly discusses morphological, syntactic and semantic features of singulatives in North Saami and other present-day Saami languages, but comparable singulatives in Khanty, Mansi and Samoyed languages as well as in Hungarian suggest that singulative expressions such as *weri-ćilmä ‘a single drop of blood’, *jäŋi-ćilmä ‘a single crystal of ice; hailstone’ and *me̮rja-ćilmä ‘a single berry’ can, in principle, be reconstructed all the way back to Proto-Uralic.